The role of transforming growth factor (TGF)-β in modulating the immune response and fibrogenesis in the gut - Biancheri, Paolo (2014)
Transforming growth factor (TGF)-b, a pleiotropic cytokine released by both immune and non-immune cells in the gut, exerts an important tolerogenic action by promoting regulatory T cell differentiation. TGF-balso enhances enterocyte migration and regulates extracellular matrix turnover, thereby playing a crucial role in tissue remodeling in the gut. In this review we describe the mechanisms by which abnormal TGF-b signaling impairs intestinal immune tolerance and tissue repair, thus predisposing to the onset of immune-mediated bowel disorders, such as inflammatory bowel disease and celiac disease. Additionally, we will discuss potential therapeutic strategies aiming at restoring physiologic TGF-b signaling in chronic intestinal diseases.